STUDIES ON MENINGOCOCCUS INFECTION : II. MONOVALENT DIAGNOSTIC SERA PREPARED FROM "FRESH" AND "STOCK" STRAINS - Rake, Geoffrey (The Rockefeller University Press, 1933)
The production of monovalent sera for agglutinin or precipitin reactions with freshly isolated strains of meningococci is described. Agglutination reactions with such sera can be carried out more rapidly, at lower temperatures and in lower dilutions, than with the standard monovalent sera prepared from stock cultures, while the results so obtained are more satisfactory owing to the relative absence of cross-agglutination.